Gonzaga Duque e Revoluções Brasileiras: um olhar para a história do Brasil - Bruna de Oliveira Fonseca (2015)
The objetive of this dissertation is to offer a different point of view about Gonzaga Duque and his publication Revoluções Brasileiras. With the goal of understanding particular features and influences in Gonzaga Duque's (1863-1911) intelectual work, an attempt to reconstitute the world in which he lived in is made, taking into consideration his personal life story, as well as the context of transformations that occurred in Brazil during the late 19th and early 20th centuries. Revoluções Brasileiras is a history textbook, in which the author offers a view of the past through a series of protests, identifying the roots of the Republic in the nation's past. Through analyzing the textbook, an attempt is made to identify Gonzaga Duque's choices and proposals regarding the history of Brazil and his thoughts on the national identity, as well as the innovations and standings compared to the intelectual traditions, with whom the author was familiar with. To identify the singularity marks and common places in Revoluções Brasileiras, the content of the textbook was compared to other writings from the same author, as well as with the following textbooks: Lições de História do Brasil, from Joaquim Manuel de Macedo; História do Brasil (Curso Superior), from Rocha Pombo. Using the publication analysis and contrasts made, we can conclude that Duque's writen history was done using traditional content and resources, wildly spread by the Instituto Histórico e Geográfico Brasileiro IHGB , with certain adaptations to achieve a new goal, form and educate youth with treasured values to the Republic. Therefore, aligning changes and stands, Revoluções Brasileiras contributed to the sedimentation of resources and arguments of common ground of the enthusiasts of the Brazilian Republic.